One Hundred Years of Surrealism – despite Schuster? Dominant Paradigm, ‘Historical’ Criticism and Critical History after 1969 (ENTHYMEMA, 2024)
A spectre is haunting criticism: the spectre of surrealism. All the powers of old criticism have entered into a holy alliance to exorcise this spectre: the “pope of surrealism” and Sartre; Nadeau and Schuster; the Revolutionary Surrealists and the Situationists. Which opposition, among his opponents, had not accused it of being outdated, or even dead during its lifetime? Which one, in turn, had not hurled back the branding reproach of surrealism to its opponents of all kinds? Two things result from this fact: I) Surrealism is already acknowledged by all the powers of criticism to be itself a power. II) Thus, it is better to reduce it to the tale of a spectre, despite the concrete expressions that the surrealists of various nationalities expose to the whole world. The historiography criticism of surrealism – this one remaining little known after 1969 – requires a critical comparative approach to the dominant paradigm.
Keywords: Surrealism; History; Historiography; Comparative criticism; Bounoure